Relationship between regional food and hypertension in the East of Turkey - Önen, Cihan; Güneş, Gülsen (International Journal Of Community Medicine And Public Health, 2019)
Background: It is important to focus on behavioral risk factors, such as harmful habits, unhealthy diet, for hypertension. In the study the aim is to examine the hypertension frequency of adults in Bitlis city center, factors affecting this and other related factors. Methods: The target population of the cross-sectional research consists of people aged 30 and higher in Bitlis city center. Face to face interviews were performed with people incorporated to the sample between February 15th and April 15th 2015 time interval in order to collect data from the field. Results: Hypertension frequency was found to be 35.5%. 59.3% of the people with hypertension are aware of the situation. The blood pressure of 26.3% of the people who are aware of their situation is under control. Significant difference was determined between hypertension and consumption frequency of regional foods such as fried fish, local cheese, fish Basma and Kurut. In logistic regression analysis significant relation was determined between hypertension and old age, women, obesity≥30 and Kurut frequent consumption. Conclusions: In the research the hypertension frequency was found to be 35.5%. Significant relation was detected between hypertension and frequent consumption of Kurut which is a regional food.